In-Hospital Outcomes of Acute ST Elevation Myocardial Infarction in Patients with Acute Kidney Injury - Haque, Md Mosharul; Ali, M Atahar; Aziz, Mustafizul; Ullah, Mohammad; Hossain, Mohammad Anowar; Islam, Md Shariful; Khair, Abul; Islam, Md Rezawanul; Afroz, Fahdia; Amin, Mohammad Ruhul; et al. (Cardiovascular Journal, 2018)
Background: Acute kidney injury (AKI) is a risk factor for long-term adverse outcomes, including acute myocardial infarction and death. The objective of this study was to find out in-hospital outcomes in patients with acute ST elevation myocardial infarction with acute kidney injury. Methods: A total 190 patients were included in this study and were equally divided into two groups, Group-I (with AKI) and Group-II (without AKI), according to absolute changes of serum creatinine level. AKI was defined as absolute changes in serum creatinine (SCr. at 48 hours’ minus admission SCr) and categorized as mild AKI (increase of 0.3 to <0.5 mg/d), moderate AKI (increase of 0.5 to <1.0 mg/dl), and severe AKI (increase of e”1.0 mg/dl) using Acute Kidney Injury Network (AKIN) criteria. Results: Overall in-hospital mortality rate was 14.7% in Group-I (mortality rate for those with mild, moderate, and severe AKI were 7%, 13.3%, and 31.8%) compared with 5.3% in Group-II. Regarding inhospital morbidities, significant arrhythmia (29.5%) was the most common complication followed by acute heart failure (18.9%), cardiogenic shock (12.6%), and mechanical complications (4.2%) which were more in Group-I compared to patients with Group-II. After adjustment of other risk variables, the multivariate logistic regression analysis revealed AKI remained an independent predictor of in-hospital mortality with adjusted odds ratios (OR) was 4.991 (95% confidence interval, 1.873-13.301). Conclusions: AKI is an independent predictor of in-hospital mortality and morbidity. It emphasizes the importance of efforts to identify risk factors and to prevent AKI during in-hospital management of acute STEMI patients. Cardiovasc. j. 2018; 11(1): 59-66